Implementation of the Fe Tablet Program for Pregnant Women - Aniesah Amieratunnisa (Journal of Public Health Indonesian, 2024)
The results of the 2018 RISKESDAS stated that 48.9% of pregnant women in Indonesia have anemia. This shows that the prevalence of anemia in pregnant women is still quite high in Indonesia. This figure tends to increase compared to the results of the 2013 RISKESDAS where the prevalence rate was 37.1%. The purpose of the study was to analyze the implementation of the program for providing Fe Tablets to pregnant women in the Jepara Regency Health Center area. This study was conducted qualitatively. The subjects of the study were 14 main informants and triangulation selected based on inclusion criteria and purposively. This study applied an interactive data analysis method. The results showed that the implementation of providing Fe Tablets to pregnant women experienced obstacles. The difference in the high and low levels of providing Fe Tablets to pregnant women was influenced by the understanding of village midwives, IEC media, and the availability of Fe Tablet stock. Suggestions from this study are that health centers need to make more effective innovations in promoting the importance of consuming Fe Tablets during pregnancy and there needs to be improved planning in the district pharmacy warehouse so that the stock of Fe Tablets is always sufficient for all health centers in Jepara Regency.